Effects of Solanum torvum fruit water extract on hyperlipidemia and sex hormones in high-fat fed male rats - Wannasiri S. (2017)
© 2017 Hainan Medical University Objective To study the effect of water extract of Solanum torvum (S. torvum) on blood lipid and sex hormone levels in high-fat diet (HFD) fed male rats. Methods Male Wistar rats were maintained on a standard diet or HFD for 10 weeks. During the last 4 weeks, the standard diet groups received distilled water or S. torvum (400 mg/kg) and the HFD groups received distilled water or S. torvum (100, 200 and 400 mg/kg). Body weight, lipid profiles, sex hormone, internal organs weight and liver histopathology were all measured. Moreover, kidney function was evaluated using blood urea nitrogen and creatinine levels, and liver function by the levels of aspartate aminotransferase and alanine aminotransferase. Results The result showed that rats in the HFD control group had increased body weight and hyperlipidemia, but had decreased levels of both testosterone and estradiol. When receiving the S. torvum extract at a dose of 100 mg/kg, treated rats had significantly increased sex hormone levels of both types, and decreased total cholesterol levels, and at a dose of 200 mg/kg, treated rats had significantly decreased levels of triglyceride. Long term administration of the S. torvum did not produce any toxic signs in livers and kidneys. Pathological examinations of livers showed lipid accumulation in the HFD group, but the treatment of S. torvum slightly reduced lipid deposition in liver tissue. Conclusions S. torvum extract can reverse the level of sex hormones to their normal level and reduce serum cholesterol in HFD-induced obese male rats. Furthermore, the long term oral administration of S. torvum extract is harmless.